2014
DOI: 10.1063/1.4868223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Penning effect on the plasma features in a non-equilibrium atmospheric pressure plasma jet

Abstract: Non-equilibrium atmospheric pressure plasma jet (APPJ) is a cold plasma source that promises various innovative applications. The influence of Penning effect on the formation, propagation, and other physical properties of the plasma bullets in APPJ remains a debatable topic. By using a 10 cm wide active electrode and a frequency of applied voltage down to 0.5 Hz, the Penning effect caused by preceding discharges can be excluded. It was found that the Penning effect originating in a preceding discharge helps bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 31 publications
(47 reference statements)
1
16
0
Order By: Relevance
“…The electrode structure is shown in Fig. 2 which is the same as the electrode system used in our previous work 9 . The wider HV electrode with width of 10 cm is mainly used to eliminate the influence of discharge in DBD zone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrode structure is shown in Fig. 2 which is the same as the electrode system used in our previous work 9 . The wider HV electrode with width of 10 cm is mainly used to eliminate the influence of discharge in DBD zone.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work 9 , we tried to interpret the abovementioned disagreement by providing some convincing experimental evidences. Based on it, in this paper, we would like to give a further demonstration and analysis to understand the formation and evolution of plasma “bullet” with hollow structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further interpretations were not obtained. Moreover, considering the Penning effect, the investigation of Chang et al [18] showed that filamentous discharge for pure Ar APPJ will transform into the same discharge morphology of pure He APPJ if a little ammonia (NH 3 ) is added into pure Ar. Therefore, electrical and optical properties of He APPJ and Ar/NH 3 APPJ are investigated in the present paper to generate a glow-like APPJ, and then the basic characteristics of glow-like APPJ are summarized.…”
Section: Introductionmentioning
confidence: 99%
“…However, by turning the Penning reactions on and off in their modes, Naidis, [19,20] and Naja et al [21] have shown that the Penning ionization is not essential for the bullets propagation and their hollow shape formation. Furthermore, Chang et al [22] reported that the annular structure of the plasma plume in ambient, in the case of He, is not due to the Penning effect on the He/air interface. To date, the mechanisms of the acceleration behavior of the plasma bullets have achieved considerable progress.…”
Section: Introductionmentioning
confidence: 99%